Managing the multi-stakeholder complex in P3 project decision-making: a mix-method review - Bakhtawar, Beenish; Mazher, Khwaja Mateen; Thaheem, Mohammad Jamaluddin; Hongyu, Jin; Narbaev, Timur; Aziz, Mubashir; Ghaithan, Ahmed M.; Mohammed, Awsan (Journal of Civil Engineering and Management, 2025)
Managing stakeholders in a public-private partnership (P3) project is complex; it involves uncertainties, variations, and intricacies. A typical P3 system has a dynamic multi-stakeholder system requiring active project management to avoid delays, conflicts, and partnership failures. Presently, limited research has explored stakeholder management in P3 projects. The current study uses bibliometric and scientometric analyses to identify stakeholder-related issues in P3 decision-making. A keyword co-occurrence and clustering reveal that project stakeholders strongly influence significant P3 decision-making in risk management, concession design, procurement, and sustainability. Therefore, a detailed content analysis is conducted to discuss this in detail. The study reveals that poor structuring of roles and responsibilities, public opposition, information asymmetry, principal-agent problems, knowledge management, and corruption are crucial stakeholder issues in decision-making. Further, a systems thinking framework is used to study the stakeholder dynamics for early engagement and relationship management for P3 projects. Lastly, the study findings are summarised as a conceptual framework of stakeholder-related issues with corresponding stakeholder management process steps. The review contributes to inclusive stakeholder management for P3 projects, helping early-stage researchers and practitioners. They can develop a more profound domain knowledge of P3 stakeholder-related issues, decision-making aspects, and stakeholder management elements.